On the importance of systematic risk factors in explaining the cross-section of corporate bond yield spreads - King, Tao-Hsien Dolly; Khang, Kenneth (Journal of Banking & Finance, 2005)
In this paper we examine the importance of systematic equity market factors in explaining the cross-sectional variation in yield spreads on corporate debt. Based on a sample of 1771 corporate bonds over the period from January 1985 to March 1998, we find that once the default-related variables are controlled for, bond betas or sensitivities to aggregate equity market risks have very limited explanatory power. This is in contrast to [Elton, E.J., Gruber, M.J., 2001. Explaining the rate spread on corporate bonds. Journal of Finance 56, 247–277] who find that market factors tied to expected returns are predominantly important, but who do not control for these variables (i.e. the relevant variables from structural models), possibly biasing their estimates. On the other hand, our finding that the systematic factors exhibit some limited explanatory power suggests that the standard contingent claims approach may not fully apply. This finding is consistent with previous research that bond betas are not completely irrelevant once market frictions are introduced. Overall, the evidence provides empirical support for the proposition that structural models capture important elements of corporate bond yield spread determination and equity market systematic factors are by no means predominant.